A highly selective fluorogenic substrate for imaging glutathione S-transferase P1: development and cellular applicability in epigenetic studies. Issue 56 (25th June 2019) - Mori, Masaya; Fujikawa, Yuuta; Kikkawa, Manami; Shino, Moeho; Sawane, Mei; Sato, Shiho; Inoue, Hideshi
Abstract : A highly selective fluorogenic substrate was designed for the specific visualization of intracellular GSTP1 activity in cancer cells. Abstract : Pi-class glutathione S-transferase (GSTP1) is a molecular marker enzyme whose expression level is altered in various malignant tumour tissues. Herein, we report the first highly selective fluorogenic GSTP1 substrate, Ps-TG, and its membrane-permeable derivativePs-TAc, for specific visualization of intracellular GSTP1 activity in cancer cells or epigenetically regulated GSTP1 expression.